Postawy i opinie studentów Wydziału Studiów Politycznych Wyższej Szkoły Biznesu - NLU w Nowym Sączu na temat zjawiska eutanazji - Jarek, Anita (My University, 2011)
Liczne dyskusje pojawiające się w mass mediach wśród przedstawicieli różnych religii, polityków, lekarzy czy prawników skłaniają do zainteresowania się tematyką śmierci na życzenie. Eutanazja jest zadaniem śmierci osobie nieuleczalnie chorej umotywowane skróceniem jej cierpień. Obszar badań autorskich obejmuje poznanie postaw studentów na temat zjawiska eutanazji. Na drodze badań ankietowych przeprowadzonych wśród studentów Wydziału Studiów Politycznych Wyższej Szkoły Biznesu - NLU w Nowym Sączu wykazano, iż studenci mają podzielone zdanie dotyczące powyższego zagadnienia. W opinii ankietowanych zjawisko śmierci na życzenie jest niezgodne z wartościami, które wyznają, mimo to, badani twierdzą, iż istnieją okoliczności usprawiedliwiające eutanazję. Na podstawie deklaracji studentów, można stwierdzić duże przyzwolenie co do zjawiska eutanazji.

Numerous discussions in mass media among different representatives of religions appearing, politicians, physicians if (or) they incline for interest on wish lawyers topic of death. Euthanasia is motivated deaths ill abbreviation of (reduction of) suffering task person incurably . Area of author research includes knowledge of posture of student about phenomenon of euthanasia. On way of questionnaire research carried among students of departments of political studios of (studies of) high school of business it exert in new - NLU Sączu, that students have divided opinion (sentence) concerning above-mentioned question. Phenomenon of death is with values in opinion questionnaires on wish incompatible, which (who) profess, in spite of it, researched fortress, that circumstances exist justifying euthanasia. On base of declaration of student, it is possible to ascertain big consent for phenomenon of euthanasia that.
Attitudes and opinions of students of the Faculty of Political Studies, School of Business - NLU in Nowy Sacz on the phenomenon of euthanasia
Keywords: eutanazja; cierpienie; pacjent; lekarz; nieuleczalnie chory; mass media; euthanasia; suffering; patient; doctor; incurably ill